(untitled) (Damu Journal of Sport Sciences, 2024)
The aim of the research was to identify the reality of organizational normalization of technical supervisors in sports and school activities for Baghdad Education Directorates. The human field was: technical supervisors working in the Education Directorate of Baghdad Governorate. The time field was: for the period from 3/7/2024 to 8/13/2024. The spatial field was: Education Directorates in Baghdad Governorate (Karkh - Rusafa). The current research community consisted of technical supervisors working in Baghdad Education Directorates (Karkh / Rusafa). The number of (166) technical supervisors distributed over the six directorates. The research sample was taken intentionally for all technical supervisors at a rate of (100%). The conclusions were: There is clear training work by the educational supervision directorates to increase the ability of technical supervisors. There are practical training courses by the Sports Activities Directorate that include developmental strengthening courses for technical supervisors. Directors use advanced communication methods to convey information correctly to learners. Directors work to develop the abilities of trainees in a scientifically correct manner that is consistent with the requirements of the labor market. Correct understanding by directors of technical supervisors helps improve the level of work.